STRUCTURAL RESPONSE OF SUBSEA PIPE ELBOWS UNDER MONOTONIC AND CYCLIC LOADING - Varelis G.E., Dib E., Karamanos S.A. (Volume 3: Materials Technology; Pipelines, Risers, and Subsea Systems, 2022)
Pipe bends (elbows) are commonly used components in subsea piping systems. They are quite flexible compared to the corresponding straight pipes and are used to reduce the reaction forces and moments at the supports and the bending moments within the piping system, as well as to accommodate pipeline thermal expansion requirements. Because of their flexibility though, they develop significant deformations, mainly in the form of cross-sectional deformation (ovalization), w h i c h are associated with the development of local stresses and strains, significantly larger than those in the corresponding straight pipe, and may cause either buckling or rupture of the elbow pipe wall. Several works have been reported on the structural performance and integrity of elbows in piping systems, in power plants or process industries. Under extreme loading conditions, e.g. seismic, or under shutdown/startup conditions, those elbows are subjected to bending under internal pressure, which may cause either plastic collapse or fracture due to low-cycle fatigue. On the other hand, the response of externally pressurised thick-walled elbows used in subsea systems, has received m u c h less attention. The main feature in those elbows is the presence of external pressure, which has a destabilizing effect, especially in deep water applications. Under monotonic load, in the presence of external pressure, elbow ovalization is accentuated leading to pipe collapse at relatively low levels of structural loading. Under cyclic loading, progressive ovalization of the elbow occurs due to accumulation of plastic deformation, which may also result in rapid collapse due to the presence of external pressure. The present paper, motivated by the use of steel elbows in subsea systems, describes a finite element simulation of elbow response under static and cyclic loading, in the presence of external pressure. Particular emphasis is given on the constitutive model, which should be capable of simulating the response of steel material under cyclic loading, ...